Continuing library education needs of library personnel in selected government agencies in Metro Manila an assessment - Orogo, Cecilia T. (1990)
The primary concern of this study was to assess the continuing library education needs of the government library personnel in order that sponsoring library organizations may plan and come up with relevant continuing education programs for them. These programs will, in effect, help upgrade the government libraray personnel's knowledge and skills in providing service to library users.